Hidden link between endocrine-disrupting chemicals and pediatric obesity - Min Won Shin; Shin-Hye Kim (Clinical and Experimental Pediatrics)
The increasing prevalence of pediatric obesity has emerged as a significant public health concern. Among various contributing factors, exposure to endocrine-disrupting chemicals (EDCs) has gained recognition for its potential role. EDCs, including bisphenols, phthalates, per- and polyfluoroalkyl substances, polycyclic aromatic hydrocarbons, and organochlorines, disrupt hormonal regulation and metabolic processes, contributing to alterations in fat storage, appetite regulation, and insulin sensitivity. This study offers a comprehensive review of the current research linking EDC exposure to pediatric obesity by integrating the findings from experimental and epidemiological studies. It also addresses the complexities of interpreting this evidence in the context of public health, highlighting the urgent need for further research.